Pharmacokinetic profile of carbamazepine and its metabolites on Javanese and Chinese ethnics in Indonesia - Djojosaputro, Mulyadi; ., Sugiyanto; Hubeis, A. Aziz; Ismadi, M. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Carbamazepine (CBZ) is an anticonvulsant widely used for epilepsy treatment. However, it is difficult to establish suitable dosage regimens for this drug because of the variation on its pharmacokinetics profiles. A lot of evidences indicate that ethnic differences may affect pharmacokinetics and hence dosage requirements. The study was conducted to document pharmacokinetic profile of CBZ and its metabolites on Javanese and Chinese ethnics in Indonesia. The study was carried out in 26 Javanese and 24 Chinese ethnics healthy volunteers, Blood samples were collected serially. Carbamazepine and its metabolites was assayed by HPLC. The results showed that no significant differences in pharmacokinetic parameters were observed between both ethnics. The values of AUC0- , Cmax, Tmax, and t1/2 CBZ on Javanese ethnic are 652.44 ± 254.79 µg/mL.h, 8.93 ± 3.58 µg/mL, 11.53 ± 2.16 h, and 43.70 ± 12.50 h respectively, while on Chinese ethnic are 830.27 ± 809.57 µg/mL.h, 13.29 ± 17.46 µg/mL, 9.97 ± 2,90 h, and 41.27 ± 13.50 h, respectively. However, a significant interindividual variation in CBZ metabolism was observed in both ethnics as shown in its large variation in metabolic ratio. The metabolic 10,11-epoxide CBZ and trans-10,11 CBZ concentration ratio on Javanese ethnic are 0.07 ± 0.03 and 0.13 ± 0.14, while on Chinese ethnic are 0.35 ± 0.99 and 0.14 ± 0.11. It can be concluded, that the Pharmacokinetic of CBZ and its metabolites on Javenes ethnic is not different compared to Chinese ethnic. In addition, there is a significant interindividual variation in pharmacokinetics profile on both ethnics.Key words: Carbamazepine, Javanese, Chinese, pharmacokinetics, epilepsy